2010
DOI: 10.2337/db09-1552
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted Disruption of Pancreatic-Derived Factor (PANDER, FAM3B) Impairs Pancreatic β-Cell Function

Abstract: OBJECTIVEPancreatic-derived factor (PANDER, FAM3B) is a pancreatic islet-specific cytokine-like protein that is secreted from β-cells upon glucose stimulation. The biological function of PANDER is unknown, and to address this we generated and characterized a PANDER knockout mouse.RESEARCH DESIGN AND METHODSTo generate the PANDER knockout mouse, the PANDER gene was disrupted and its expression was inhibited by homologous recombination via replacement of the first two exons, secretion signal peptide and transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 27 publications
3
60
1
Order By: Relevance
“…Pancreatic islets obtained from the PANDER knockout mouse (PANDER KO) displayed an impaired glucose stimulated insulin secretion (GSIS) (Robert-Cooperman et al, 2010). The mechanism for this decreased biological function has yet to be determined precisely, although the observed inhibited intracellular Ca 2+ response is believed to have a role in the impaired GSIS of the PANKO model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic islets obtained from the PANDER knockout mouse (PANDER KO) displayed an impaired glucose stimulated insulin secretion (GSIS) (Robert-Cooperman et al, 2010). The mechanism for this decreased biological function has yet to be determined precisely, although the observed inhibited intracellular Ca 2+ response is believed to have a role in the impaired GSIS of the PANKO model.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade PANcreatic-DERived factor (PANDER or FAM3B) has been investigated with regard to secretion from the endocrine pancreas and biological impact on glycemic regulation both in-vitro and in-vivo (Zhu, Xu, Patel et al, 2002, Burkhardt, Cook, Young et al, 2008, Burkhardt, Greene, White et al, 2006, Cao, Yang, Burkhardt et al, 2005, Hou, Wang, Li et al, 2011, Mou, Li, Yao et al, 2013, Robert, 2005, Robert-Cooperman, Carnegie, Wilson et al, 2010, Wang, Cai, Pang et al, 2008, Xiang, Chen and Yang, 2012, Xu, Gao, Wu et al, 2005, Yang, Gao, Robert et al, 2005, Yang, Robert, Burkhardt et al, 2005, Zhuang, Guan, Gao et al, 2011). Our recently generated pancreas specific overexpressing transgenic mouse model (PANTG) exhibits both fasting and fed glucose intolerance primarily attributed to impaired hepatic insulin signaling concordantly coupled with both increased gluconeogenesis and lipogenesis (Robert-Cooperman, Dougan, Moak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining and confocal microscopy assays further revealed that FAM3B protein is specifically localized in the islets within the pancreas . Therefore, FAM3B is also called PANDER in subsequent studies . Human and mouse PANDER proteins are composed of 235 amino acid residues with a 29‐amino acid N‐terminal signal peptide and share high‐sequence homology among species.…”
Section: Fam3b (Pander) and Nafldmentioning
confidence: 99%
“…These studies strongly indicate that the expression and secretion of PANDER and insulin are tightly coupled in β cells, which is critical in the maintenance of β cell function. In support, PANDER gene deficient ( PANDER −/−) mice show glucose intolerance because of impaired insulin secretion from pancreatic islets, and isolated PANDER −/− islets exhibit blunted insulin secretion in response to glucose or potassium chloride challenge when compared with PANDER +/+ islets . Furthermore, mutation of Tyr26 and Leu27 in the signal peptide of PANDER, which enhances PANDER secretion, is associated with increased insulin secretion in β cells in the absence or presence of low glucose stimulation .…”
Section: Fam3b (Pander) and Nafldmentioning
confidence: 99%
See 1 more Smart Citation